PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA BANK MILIK PEMERINTAH (BUMN) YANG TERDAFTAR DIBURSA EFEK INDONESIA - Handayani, Pebri; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to test partially and simultaneously the effect of profitability and leverage on firm value. The ratio used in measuring Profitability as an independent variable is Return On Assets (ROA), Return On Equity (ROE), Operational Costs and Operational Opinion (BOPO). The ratio used in measuring Leverage is Capital Adequacy Ratio (CAR), and Primary Ratio (PR). Meanwhile, the ratio used to measure Company Value is Price Book Value (PBV) and Price Earning Ratio (PER). The method used to observe the effect of profitability and leverage on firm value is by using simple linear regression and multiple linear regression. The data used in this study are secondary data, financial reports and annual report annual report. The data is listed on the Indonesia Stock Exchange (IDX) for 8 years from the period 2010 to 2017. Sampling was done by saturated sampling, which used were 4 companies. Data analysis uses simple linear regression analysis, multiple linear regression, t test, f test, and determination test coefficient. This data uses linear regression analysis with SPSS 22. The results of this study indicate that the profitability variable partially (t test) not have a significant effect on firm value, while the leverage variable does has a significant effect on firm value on state-owned banks listed on the Indonesia Stock Exchange. The results of simultaneous research (F test) indicate the influence of the variable profitability and leverage on the value of the company on state-owned banks (BUMN) listed on the Indonesia Stock Exchange. Keywords: profitability, leverage and company value.